2011
DOI: 10.1099/mic.0.042929-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of healthy children by Moraxella catarrhalis is characterized by genotype heterogeneity, virulence gene diversity and co-colonization with Haemophilus influenzae

Abstract: The colonization dynamics of Moraxella catarrhalis were studied in a population comprising 1079 healthy children living in Rotterdam, The Netherlands (the Generation R Focus cohort). A total of 2751 nasal swabs were obtained during four clinic visits timed to take place at 1.5, 6, 14 and 24 months of age, yielding a total of 709 M. catarrhalis and 621 Haemophilus influenzae isolates. Between January 2004 and December 2006, approximate but regular 6-monthly cycles of colonization were observed, with peak coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 52 publications
(70 reference statements)
9
46
3
2
Order By: Relevance
“…From the results it is noteworthy that in contrast to the infectious process of some other body systems, the URTI, particularly rhinosinusitis, ethmoiditis, rhinopharyngitis and adenoiditis most often (in more than 70% of cases) were with polymicrobial etiology. Similar results have also been reported in our earlier studies as well as other authors (3,4,13,14).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…From the results it is noteworthy that in contrast to the infectious process of some other body systems, the URTI, particularly rhinosinusitis, ethmoiditis, rhinopharyngitis and adenoiditis most often (in more than 70% of cases) were with polymicrobial etiology. Similar results have also been reported in our earlier studies as well as other authors (3,4,13,14).…”
Section: Discussionsupporting
confidence: 82%
“…A little known fact is that the most common microbial combination of causative agents, actually are exactly those two microorganisms in association, not only for epiglottitis but also for other URTI as adenoiditis and rhinopharyngitis in children, that have been confirmed by other authors through the last years (14).…”
Section: Discussionmentioning
confidence: 52%
“…Other researchers have reported similar associations between S. pneumoniae and H. influenzae (10,12,14), S. pneumoniae and M. catarrhalis (10,12), and M. catarrhalis and H. influenzae (10,37) in children of a comparable age. Pettigrew et al (20) found negative associations between S. pneumoniae and H. influenzae and between M. catarrhalis and H. influenzae in children with upper respiratory infections, suggesting that the presence of an active infection may influence colonization dynamics.…”
mentioning
confidence: 57%
“…This respectively. The colonization status was determined using standard M. catarrhalis culture and detection techniques [1].…”
Section: Study Cohortmentioning
confidence: 99%
“…Studies have shown that the bacterium colonizes the nasopharynx soon after birth and that the carriage rate of M. catarrhalis in healthy children may differ per geographical region, season and year of isolation [1]. For example, in a German study (November 1991 to April 1992), 9% of children attending day-care centers ranging in age from 4 months to 3 years old were colonized with M. catarrhalis [2].…”
Section: Introductionmentioning
confidence: 99%